An Analysis on Student’s Ability and Problems in Writing Recount Text at The Eighth Grade of SMPN 2 Lingsar - Aprilia, Rizkia Prahasti; Thohir, Lalu; Zamzam, Ahmad; Udin, Udin (Jurnal Ilmiah Profesi Pendidikan, 2025)
This study aims to analyze the students' ability in writing recount text, and to explore the problems they faced in writing this text type. By using a qualitative method with a case study, this research involved 28 students as samples in the VIII grade of SMPN 2 Lingsar in the academic year 2023/2024. They were selected with a purposive sampling method. The data were collected by using a set of validated questionnaires and a writing test and they were analyzed descriptively based on the purposes of this research.  The findings show that the students' abilities in writing recount text are in the poor category, with an average score of 47. The students experienced problems that cause them to make many mistakes in writing recount texts are grammar with an average score of 33, vocabulary with an average score of 28 and mechanics with an average score of 26. The students should practice writing and the teacher needs to assist the students to develop their writing skill by applying appropritate strategies.